Student’s Second-Language Grade May Depend on Classroom Listening Position - Hurtig, Anders; Sörqvist, Patrik; Ljung, Robert; Hygge, Staffan; Rönnberg, Jerker (PLOS ONE, 2016)
The purpose of this experiment was to explore whether listening positions (close or distant location from the sound source) in the classroom, and classroom reverberation, influence students' score on a test for second-language (L2) listening comprehension (i.e., comprehension of English in Swedish speaking participants). The listening comprehension test administered was part of a standardized national test of English used in the Swedish school system. A total of 125 high school pupils, 15 years old, participated. Listening position was manipulated within subjects, classroom reverberation between subjects. The results showed that L2 listening comprehension decreased as distance from the sound source increased. The effect of reverberation was qualified by the participants' baseline L2 proficiency. A shorter reverberation was beneficial to participants with high L2 proficiency, while the opposite pattern was found among the participants with low L2 proficiency. The results indicate that listening comprehension scores-and hence students' grade in English-may depend on students' classroom listening position.